An extensive reading strategy to promote online writing for elementary students in the 1:1 digital classroom. Issue 2 (17th February 2016) - Sun, Zhong; Yang, Xian Min; He, Ke Kang
Abstract : The rapid development of the digital classroom has made it possible to combine extensive reading with online writing, yet research and development in this area are lacking. This study explores the impact of online writing after extensive reading in a classroom setting in China where there was one computer for each student (a 1:1 digital classroom). Thirty-nine fifth graders from an elementary school participated in the study. These students were divided into three groups with equivalent pretest score averages. Members of each group wrote Chinese compositions online after reading in one of the following three conditions in the same 1:1 digital classroom: (1) Objective-Focused Fast Extensive Reading (OFFER), an extensive reading strategy developed for and tested in this study; (2) one-size-fits-all extensive reading; (3) zero extensive reading, using only the class textbook. Qualitative and quantitative analyses were performed using data from four sources: scores from three teacher judges, comments from those judges, comment icons from classmates, and writing speed data collected via the learning management system. The results indicated that the OFFER group showed significant superiority in writing quality and quantity compared to the other two groups. It is concluded that (1) extensive reading can be utilized not only for cultivating reading interest, but also for promoting writing, and (2) the OFFER strategy can lead to improved writing quality and fluency compared to one-size-fits-all extensive reading. Further suggestions for researchers and language teachers are proposed in the final part of the paper.